Analisis Fiqh Siyasah Terhadap Fenomena Serangan Fajar: Perspektif Hukum Islam Dalam Konteks Keamanan Pemilu - Safaruddin Safaruddin; Tafrihatul Ula (Siyasah Wa Qanuniyah, 2024)
General elections (Pemilu) are a critical milestone in the democratic system of a country, determining the selection of leaders and the political direction of the nation. However, the phenomenon of "Serangan Fajar", involving intimidation or political bribery before or on election day, poses a serious threat to the integrity of the democratic process. This study aims to analyze how Indonesian law intersects with political traditions that are illegal, such as Serangan Fajar, from the perspective of fiqh siyasah, which includes citizens' rights, state responsibilities, legal implications, and the relevant framework in addressing this phenomenon in the context of election security. The research method used is a literature review. Fiqh siyasah governs state policies based on Islamic teachings, aiming for the welfare of the community. Serangan fajar, as a form of political bribery, violates Indonesian law and is punishable by law. In Islam, bribery or risywah is forbidden and condemned by Allah SWT and the Prophet Muhammad SAW. This practice undermines democracy and contradicts the principles of justice in Islam. Therefore, strengthening election security policies by Bawaslu and encouraging active participation from the community is essential to preserve the integrity of elections.